2011
DOI: 10.1007/s12031-011-9693-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurorescue Effect of Rosmarinic Acid on 6-Hydroxydopamine-Lesioned Nigral Dopamine Neurons in Rat Model of Parkinson's Disease

Abstract: Rosmarinic acid (RA) is a naturally occurring polyphenolic compound. It has been reported that RA possessed antioxidant and anti-inflammatory properties. Our previous study showed that RA could protect MES23.5 dopaminergic cells against 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in vitro. The purpose of this study was to explore the neuroreparative (neurorescue) effect of RA on 6-OHDA-lesioned rat model of Parkinson's disease (PD) in vivo. In this study, the rats were given RA orally after intrastriatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…Reducing free-radicals from cigarette smoke by using a filter impregnated by an extract of a rosemary plant in oil was reported (Alexandrov et al 2006). Rosmarinic acid could exert its neuroprotective and anti-oxidative effects against 6-OHDA-induced neurotoxicity in dopaminergic neurons (Ren et al 2009;Wang et al 2012;Noguchi et al 2015). Our results also demonstrated that RE at dose of 50 mg/kg body weight could decrease oxidative stress by increasing the activities of SOD, CAT and GPx in hippocampus resulting in the decrease of lipid peroxidation level in lesioned region.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing free-radicals from cigarette smoke by using a filter impregnated by an extract of a rosemary plant in oil was reported (Alexandrov et al 2006). Rosmarinic acid could exert its neuroprotective and anti-oxidative effects against 6-OHDA-induced neurotoxicity in dopaminergic neurons (Ren et al 2009;Wang et al 2012;Noguchi et al 2015). Our results also demonstrated that RE at dose of 50 mg/kg body weight could decrease oxidative stress by increasing the activities of SOD, CAT and GPx in hippocampus resulting in the decrease of lipid peroxidation level in lesioned region.…”
Section: Discussionmentioning
confidence: 99%
“…Iron staining was conducted as described previously by Wang et al (Wang et al 2012). For this purpose, sections were soaked for 30 s in research grade water before staining, then incubated for 30 min in a freshly prepared solution of equal parts of 2 % HCL and 2 % potassium ferrocyanide.…”
Section: Iron Stainingmentioning
confidence: 99%
“…Besides, RA is also potentially valuable for the improvement of diabetes mellitus and obesity by inhibiting digestive enzymes, such as α-amylase and α-glucosidase (Zhu et al, 2014). Furthermore, RA has several neuronal benefits like anti-amyotrophic lateral sclerosis (ALS) (Shimojo, Kosaka, Noda, Shimizu, & Shirasawa, 2010), anti-Alzheimer's disease (AD) (Alkam, Nitta, Mizoguchi, Itoh, & Nabeshima, 2007), improving effect on experimental Parkinson's disease model (Wang et al, 2012b), nootropic effect, and anti-depressive benefit (Ito et al, 2008;Sasaki, Han, Shimozono, Villareal, & Isoda, 2013). However, the high water solubility of RA results in its poor permeation across intestinal epithelial cells and low oral bioavailability, which restricts its application as a functional food (Konishi, Hitomi, Yoshida, & Yoshioka, 2005;Konishi, Hitomi, & Yoshioka, 2004).…”
Section: Introductionmentioning
confidence: 99%